Benefits and limitations of the transfer online of Irish College of General Practitioners continuing medical education small group learning during the COVID pandemic: a national Delphi study - Stephanie Dowling; Finola Minihan; Ilona Duffy; Claire McNicholas; Gillian Doran; Pat Harrold; John Burke; Walter Cullen (Medical Education Online)
Background In Ireland and internationally, small-group learning (SGL) has been shown to be an effective way of delivering continuing medical education (CME) and changing clinical practice.Research Question This study sought to determine the benefits and limitations, as reported by Irish GPs, of the change of CME-SGL from face-to-face to online learning during COVID.Methods GPs were invited to participate via email through their respective CME tutors. The first of three rounds of a survey using the Delphi method gathered demographic information and asked GPs about the benefits and/or limitations of learning online in their established small groups. Subsequent rounds obtained a consensus opinion.Results Eighty-eight GPs across Ireland agreed to participate. Response rates varied from 62.5% to 72% in different rounds. These GPs reported that attending their established CME-SGL groups allowed them to discuss the practical implications of applying guidelines in COVID care into practice (92.7% consensus), reviewing new local services and comparing their practice with others (94% consensus); helping them feel less isolated (98% consensus). They reported that online meetings were less social (60% consensus), and informal learning that occurs before and after meetings did not take place (70% consensus). GPs would not like online learning to replace face-to face-CME-SGL after COVID (89% consensus).Conclusion GPs in established CME-SGL groups benefited from online learning as they could discuss how to adapt to rapidly changing guidelines while feeling supported and less isolated. They report that face-to-face meetings offer more opportunities for informal learning.